Organization and carrying out the triathlon competitions in Ukraine - Водлозеров, Владимир Егорович (Slobozhanskyi Herald of Science and Sport, 2016)
Vodlozerov V. Purpose: the aim is analyzing of system of organization and carrying out the triathlon competitions in Ukraine in accordance with rules of triathlon international federation. Material & Methods: comparative analysis of process of organization and carrying out the triathlon competitions in the world and Ukraine was carried out on basis of specialist literature studying, normative base of sports organizations (triathlon federation). Results: inconsistencies were identified in competitions carried out in cold season, particularity of triathlon that intends overcoming the combined distance without time durations between stages. Conclusions: recommendation in eliminate inconsistencies that affect to performance of triathlon competitions in Ukraine was suggested